The effect of different training modalities on physical fitness in women over 50 years of age - Neves, Lucas Melo; Diniz, Tiego Aparecido; Rossi, Fabrício Eduardo; Fortaleza, Ana Claudia De Souza; Horimoto, Eduardo Tomoyoshi; Geraldo, Vanessa De Oliveira; Santos, Vanessa Ribeiro Dos; Freitas Júnior, Ismael Forte (Universidade Estadual Paulista, 2016)
Abstract It is not yet clear which physical exercise protocols have greater potential to mitigate the functional decline in physical fitness (coordination, flexibility, strength, agility and cardiorespiratory capacity). Thus, the objective of this study was to compare different training modalities on physical fitness in women over 50 years of age and understand which training protocol is more effective for promoting significant improvements in physical fitness. The initial sample consisted of 79 subjects, of which 17 dropped out, resulting in a total of 62 subjects who completed the study and are included in the analysis (n = 62). The average age of the study population was 60.1±5.4 years, divided into five groups: aerobic training, concurrent training, multimodal training, functional training and control group. Physical fitness was analyzed through AAHPERD (American Alliance for Health, Physical Education, Recreation and Dance) tests (0 and eighth weeks). The ANOVA analyses (aleatory effect) show a main effect of time for coordination (p<0.001), strength (p = 0.004), agility (p<0.001) and cardiorespiratory capacity (p<0.001), and statistically significant interactions for coordination (p = 0.003) and cardiorespiratory capacity (p = 0.033). When comparing the average relative differences between the group (Δ%), significant improvement was observed in coordination and agility (p<0.001) in the multimodal and functional training groups. For cardiorespiratory fitness, there was a significant improvement in the aerobic, concurrent and multimodal training groups (p<0.001) and strength increased in the functional training group (p = 0.04). Functional training was demonstrated to be more effective at promoting significant improvements in physical fitness than the other investigated exercise protocols.
Keywords: AAHPERD; activities of daily living; exercise